Service quality dimensions affect outpatient satisfaction - Defri Fitriya Nengsih; Fatma Siti Fatimah; Choirul Anwar; Edi Sampurno Ridwan (Alma Ata University Press, 2023)
Background: Monitoring the level of patient satisfaction is the target of health agencies, in this case hospitals, to develop and compete with other hospitals. This measure is to determine the extent to which the dimensions of the quality of health services that have been prepared meet patient expectations. The increasing quality of service in a hospital is expected to be able to meet the expectations of patients so that this results in patient satisfaction. One type of health service that exists in hospitals is outpatient services which are required to provide quality services, by providing services to patients and patient families in accordance with quality standards of meeting patient needs and expectations. Objectives: To determine the influence of service quality dimensions on outpatient patient satisfaction. Methods: This type of research is quantitative with a cross-sectional research design. The population in this study were all outpatients at RSUP Dr. Soeradji Tirtonegoro. The sampling technique used in this study is probability sampling with simple random sampling. The number of samples in this study were 200 respondents. Data analysis in this study used univariate analysis, bivariate analysis with Spearman rank and chi-square statistical tests and multivariate analysis with logistic regression statistical tests. Results: The results showed that there was an influence of responsiveness and empathy dimensions on general outpatient patient satisfaction at hospital of dr. Soeradji Tirtonegoro. It is known that in the multivariate test both dimensions were affected 5 and 27 times respectively in influencing general outpatient patient satisfaction with a p-value of 0.003 and a p-value of 0.005, respectively. Conclusions: There is an influence between the dimensions of quality (Responsiveness and Empathy) on patient satisfaction outpatient at dr. Soeradji Tirtonegoro hospital